2021
DOI: 10.1093/eurpub/ckab165.552
|View full text |Cite
|
Sign up to set email alerts
|

Taboos and Myths as a mediator of the Relationship between Menstrual Practices and Menstrual Health

Abstract: Background There is a piece of growing evidence that associates menstrual practices with menstrual health. But menstruation has always been accompanied by various taboos and myths. Findings from qualitative studies have highlighted that these taboos and myths impact the psychosocial outcomes of the menstruators, ultimately affecting their menstrual health. However, no quantitative study has explored this link between menstrual practices and menstrual health. Thus, as a part of this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…COVID‐19 has exacerbated the existing silence around menstruation, and thus, it is crucial to raise awareness and break the negative social norms around menstruation (Babbar, 2021 ). It can be done by integrating MHM into offline and online learning curriculums.…”
Section: Discussionmentioning
confidence: 99%
“…COVID‐19 has exacerbated the existing silence around menstruation, and thus, it is crucial to raise awareness and break the negative social norms around menstruation (Babbar, 2021 ). It can be done by integrating MHM into offline and online learning curriculums.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently conducted meta-analysis that included 97,070 girls over 138 studies in India, it was found that around half of the adolescent girls attained menarche with little understanding of how to manage it [ 38 ]. This experience is made worse by the various myths and false beliefs about menstruation that are levied on them by their communities and families, such as prohibitions on taking a bath, using the kitchen, going to religious places, and other forms of discriminatory practices (such as untouchability and social isolation) by their family friends and close relatives [ 39 , 40 ]. Such biases and behaviours that uphold myths may severely affect girls, including their absence from school while they are menstruating and ultimately dropping out of school [ 41 ].…”
Section: Menstrual Health and Hygiene Management In Indiamentioning
confidence: 99%
“…12 13 Furthermore, although these policies represent an important step in support of gender equality, such policies are usually limited to the provision of period pads, with no menstrual education for girls or boys, often because of deeply rooted myths and taboos that code menstruation as bad, unclean, and to be hidden. 14 A further dimension for education and policy involves environmental waste, which will increase with greater access to disposable pads. Education about the environmental impact of different period products could help people make informed choices about the products they need, reduce menstrual stigma, and build reproductive health literacy and agency.…”
mentioning
confidence: 99%
“…Some studies have shown, however, that provision of products is not enough to significantly improve school attendance among girls 1213. Furthermore, although these policies represent an important step in support of gender equality, such policies are usually limited to the provision of period pads, with no menstrual education for girls or boys, often because of deeply rooted myths and taboos that code menstruation as bad, unclean, and to be hidden 14…”
mentioning
confidence: 99%